Luminescent materials in the form of glass ceramic - Salamakha, Tatsiana A.; Trusova, Ekaterina E.; Tratsiak, Yauhen V. (Journal of the Belarusian State University. Chemistry, 2020)
In this paper an original method for obtaining glass ceramic samples based on iodides of alkaline-earth elements activated by Eu2+ is proposed, their structural and spectral-luminescent properties are studied. The formation of glass ceramic samples containing both anhydrous iodides of alkaline-earth elements and crystalline hydrates of iodides of alkaline-earth element is confirmed by X-ray diffraction analysis when using in the synthesis process from 30 to 60 wt .% BaI2 : Eu2+, from 40 to 50 wt. % SrI2 : Eu2+ and 40 wt. % CaI2 : Eu2+. The possibility of adjusting the resulting color of glass ceramic samples emission (from blue to purple-red) by varying its composition is shown.
Keywords: luminescence; Eu2; glass ceramic; barium iodide; strontium iodide; calcium iodide